2019
DOI: 10.1002/cam4.1859
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum HER‐2 predicts poor prognosis in breast cancer and is correlated to ADAM10 expression

Abstract: Human epidermal growth factor receptor‐2 (HER‐2) overexpression in breast tumor tissues is associated with a poor prognosis but may benefit from treatment with trastuzumab. The extracellular domain (ECD) of HER‐2 can be measured in serum and which has been a new inspection item in clinical laboratory of several hospitals. However, whether serum HER‐2 ECD can be a marker of HER‐2 status in tumor tissues still confused clinicians. This study is a retrospective observation to explore the correlation between serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…It has also been implicated in the pathogenesis of several types of human malignant tumors including breast cancer [36]. But the roles of ADAM10 in breast cancer have been focused on the HER2 positive type [20][21][22][23] rather than on the triple-negative type [25,37]. Here, we have demonstrated that the higher level of ADAM10 in its active form is expressed not only in HER2 ampli ed cell line SK-BR-3 but also in TNBC cell lines MDA-MB-231, MDA-MB-468 and BT-549, compared with ER positive cell line MCF7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been implicated in the pathogenesis of several types of human malignant tumors including breast cancer [36]. But the roles of ADAM10 in breast cancer have been focused on the HER2 positive type [20][21][22][23] rather than on the triple-negative type [25,37]. Here, we have demonstrated that the higher level of ADAM10 in its active form is expressed not only in HER2 ampli ed cell line SK-BR-3 but also in TNBC cell lines MDA-MB-231, MDA-MB-468 and BT-549, compared with ER positive cell line MCF7.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ADAM10 contributes to HER receptor activation by shedding of HER ligands such as betacellulin and mediates Trastuzumab treatment resistance [21]. Zheng et al has also demonstrated that HER2 extracellular domain (ECD) shedding is asscociated with α-secretase activity of ADAM10 in breast cancer tissues and cell lines [22]. MEL-18 depletion induced trastuzumab resistance by increasing ADAM10/17 mediated ErbB ligand production and receptor heterodimerization in HER2 positive breast cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been implicated in the pathogenesis of several types of human malignant tumors including breast cancer [36]. However, the studies on the roles of ADAM10 in breast cancer have only focused on the HER2 positive type [20][21][22][23] rather than on the triplenegative type [25,37]. Here, we have demonstrated that the higher level of ADAM10 in its active form is expressed not only in HER2 ampli ed cell line SK-BR-3 but also in TNBC cell lines MDA-MB-231, MDA-MB-468 and BT-549, compared with ER positive cell line MCF7.…”
Section: Discussionmentioning
confidence: 99%
“…Increased shedding of HER2 into a soluble form, HER2-extra cellular domain (ECD) by ADAM10 has recently been shown to be predictive of reduced progressionfree survival (74). In 545 HER2 positive invasive ductal mammary carcinoma (NST) patients, it was found that a high serum HER2-ECD relative to tumor HER2 level was predictive of reduced progression-free survival (74). Feldinger et al demonstrated that after treatment with trastuzumab, ADAM10 levels increased both in vitro and in vivo using PDX (75).…”
Section: Breast Cancermentioning
confidence: 99%